A Literature Review: Management of Paralysis and Prevention of Acute Respiratory Failure in Guillain-Barré Syndrome - Al Qindi, Ahmad Sa'Bi; Senna, Cantika Brilliant; As Shiddiq, Muhammad Hilmy; Yolanda B.S, Moh. Rizky; Zulkifli, Yasmin Sabrina; Belia, Prima (Jurnal Biologi Tropis, 2026)
Guillain-Barré Syndrome (GBS) is an acute immune-mediated disorder of the peripheral nervous system characterized by progressive muscle weakness and paralysis. In severe cases, respiratory muscle involvement may lead to acute respiratory failure, which remains one of the leading causes of morbidity and mortality in patients with GBS. This literature review aims to discuss the pathophysiology, clinical manifestations, diagnostic approaches, management of paralysis, and strategies for preventing acute respiratory failure in Guillain-Barré Syndrome. A literature review was conducted by analyzing scientific journal articles, textbooks, and international clinical guidelines retrieved from electronic databases. The findings indicate that GBS is the most common cause of acute non-traumatic flaccid paralysis worldwide and is frequently preceded by an infectious illness. Diagnosis is primarily established based on clinical features and supported by cerebrospinal fluid analysis and electrodiagnostic studies, with diagnostic certainty commonly assessed using the Brighton Collaboration Criteria and clinical evaluation guided by the National Institute of Neurological Disorders and Stroke (NINDS) criteria. Respiratory complications occur in approximately 20–30% of patients and often require intensive monitoring and mechanical ventilation. Early recognition of respiratory muscle weakness through serial assessment of respiratory function, prompt airway management, and timely ventilatory support are essential to prevent acute respiratory failure and improve clinical outcomes. A multidisciplinary approach involving neurologists, intensivists, pulmonologists, rehabilitation specialists, and nursing teams is crucial for reducing morbidity and mortality associated with GBS.